La recepción de la cultura italiana en La Ilustración Española y Americana - Assunta Polizzi (Cahiers de Civilisation Espagnole Contemporaine)
This study analyzes the various references to Italy in several sections of La Ilustración Española y Americana in order to assess the contribution of the magazine in the configuration of the reception of Italian culture in Spain in the late nineteenth century, through the newspaper and through network of textual features associated therewith.